Social Accountability and Service Delivery Effectiveness: What is the Evidence for the Role of Sanctions? Background Paper - Aston, Tom; Zimmer Santos, Grazielli (2022)
Executive Summary Understanding how civil society can get government t o respond to their needs, preferences and demands, and deliver goods a nd services to citizens is a central concern in social accountability initiatives. It is widely argued that sanctions make a key difference to service delivery outcomes, and that without them, transparency and accountability interventions are less likely to be effective and less likely to be sustainable (Anderson et al., 2020; Arugay, 2016; Fox, 20 20; Goetz and Jenkins, 2005; Grandvoinnet et al., 2015; McGee and Gave nta, 2011; Molina et al., 2017; Joshi, 2010; Joshi, 2017; Tsai et al. 2019). In this paper, sanctions refer to the threat or imposition of a punishment for transgressing a rule or norm. Yet, what evidence is th ere to support the claim that sanctions are king? How much do we actua lly know about social and formal sanctions and their effectiveness in improving service delivery? Looking at 11 meta-reviews and 35 cases, t his background paper sheds light on these questions and the conditions under which sanctions promoted within social accountability intervent ions may have contributed to improved service delivery. Sanctions, bot h social and formal, feature very prominently in the scholarly literat ure related to accountability, so much so that some scholars have argu ed that it has become synonymous with punishment (Mansbridge, 2014; Sc hedler, 1999). While it may not be true that these concepts are fully synonymous, this trend in scholarship significantly influenced the thi nking of donors such as the Department for International Development ( DFID) and the World Bank over the last two decades (Grandvoinnet et al ., 2015; Malena and McNeil, 2010; Moore and Teskey, 2006; World Bank, 2003). As a result, sanctions also feature in the dominant models, or theories of change, in the social accountability sector. Yet, in revie wing 11 meta-reviews in the transparency and accountability sector we found that while there is plenty of theoretical argument asserting the potential effectiveness of social and formal sanctions, there was lim ited empirical evidence to support the claim that sanctions were key. Our review of 35 cases revealed five mechanisms of change related to s ocial and formal sanctions. These were: (i) “sticks” – response to pun ishment; (ii) “big brother is watching” – response to threat of formal punishment; (iii) diagonal accountability – response to threat of for mal punishment by horizontal accountability agencies; (iv) litigation – response to legal investigations or lawsuits supported by community paralegals and legal aid organizations and; (v) response to “naming an d shaming” by civil society and/or media. We challenge the dominant vi ew in scholarship that harder social sanctions and enforcement of stro nger formal sanctions are either necessary to the achievement of highe r-level service delivery outcomes or that they will deliver better and more sustainable outcomes. We find that both social and formal sancti ons can contribute to improving service delivery outcomes across a var iety of country contexts. In half of the 35 cases reviewed, we were ab le to establish a likely link between social or formal sanctions and i ntermediate effects over the short term with some degree of confidence . These effects ranged from increased service provider awareness and m otivation, increased availability of funding, staff, and materials, to improved infrastructure quality, and in a minority of cases impact le vel changes such as improved test scores. However, the role of sanctio ns in delivering outcomes was often unclear, outcomes were almost neve r sustainable, and in close to half of the 35 cases reviewed there wer e substantial negative effects. These effects ranged from reducing tra nsparency and funding, to discrediting, relocating, and reprisals for advocates and whistle-blowers, threats of violence to collaborating go vernment actors, damaging staff morale, reducing attendance, and gener ating conflict among staff and between staff and community members and between staff and patients, damaging trust. There are therefore some serious ethical dilemmas associated with sanctioning efforts which nee d to be carefully considered. We argue that imposing sanctions without building relationships or systems to promote good behavior is unlikel y to improve service delivery outcomes in a sustainable way. Another, perhaps surprising, finding was that there are some actors that are re gular targets of sanctions, and in many cases, these actors are a lot weaker than is commonly assumed. Three broad types of actors were the most common targets of punishment: (i) absentee nurses or teachers who had their pay or allowances reduced; (ii) offending officials who wer e either suspended, relocated, or fired; and (iii) contractors who had to cover the cost of rejected materials or faced lawsuits, alongside civil servants involved in contracting. We suggest that closer relatio nships may perhaps reduce stakeholders’ appetite to impose sanctions. Particularly in the health sector, we found that more proximate relati onships created disincentives for confrontation, and in such circumsta nces, a “policing” approach to monitoring was also deemed inappropriat e and counterproductive. Conversely, it seems that actors generally pr efer to sanction “others,” i.e., when an actor/organization was outsid e the group. Short-term consultants, contractors, and suppliers were e asy (and quite vulnerable) targets for harder sanctions. It has also b een argued that there may be productive combinations of collaborative and confrontational tactics?—?i.e., hybrids. We found that many suppos ed confrontational and collaborative hybrids were, in fact, dislocated in time and space. Many so-called “inside-outside” strategies, theref ore, seem to be a potential mischaracterization. We also found, as Fun g and Wright (2003) argued nearly two decades ago, that adversarial fo rms of engagement cannot easily be redeployed for collaborative purpos es. It is widely argued that supposedly ‘weaker’ forms of citizen enga gement are less effective than those with ‘strong enforceability (McGe e and Gaventa, 2011).’ We found no compelling evidence to support this contention. A quarter of cases reviewed were collaborative for certai n periods or in certain locations. On average, these were slightly mor e successful when compared with periods or locations when imposing san ctions was a key strategic emphasis. So, soft power can also be powerf ul. Rather than one approach necessarily being superior (confrontation al, collaborative, or hybrid) however, we argue that the best approach is likely to be the one most appropriate to the context. While we wer e unable to identify strong trends of contextual factors which enabled social and formal sanctions to play a role in enhancing service deliv ery, we were able to identify several conditions which we believe offe r the greatest promise. These conditions were: (i) supportive leaders who played a role as champions; opening doors or accompanying civil so ciety efforts; (ii) high capacity and legal authority of oversight age ncies; (iii) competitive elections, which provided windows of opportun ity for CSOs to combine political and social accountability efforts, a nd; (iv) vulnerable public servants and service providers already in r elatively precarious situations and are thus easy targets. Overall, ou r study finds that sometimes sanctions can be effective, but punishmen t is not the answer to all the world’s problems. Given these limitatio ns, we recommend that it is time to reconsider “carrots” and enquire f urther into the enabling conditions for bureaucrats and service provid ers. Relatedly, scholars, evaluators, and program teams should look mo re closely at service providers’ or civil servants’ motivations and ta ke context into account more seriously. To uncover these contextual an d motivational features, we believe that scholars, evaluators, and prp rogrameams should also make better use of theory-based and participato ry methods. And perhaps most importantly, donors and practitioners sho uld carefully consider and mitigate the potential for backlash from sa nctions-based approaches.